Studies on North American Carboniferous Insects. 2. The Genus Brodioptera, From the Maritime Provinces, Canada - F. M. Carpenter (Psyche: A Journal of Entomology)
Although few in number, the insects which have been found in the Upper Carboniferous strata of the Maritime Provinces of Canada are of exceptional interest. They occur in rocks which are well down in the Westphallan stage (Zone A) and are therefore only a little younger than the oldest insects known (Namurian). In 1957, Dr. M. J. Copeland of the Canada Department of Mines and Technical Surveys published an account of the arthropod fauna of the Upper Carboniferous rocks of these provinces and included descriptions of two species of the genus Brodioptera, which he placed in the Order Megasecoptera. Since Dr. Copeland's descriptions and illustrations are inadequate for our present needs of interpreting the relationships of these insects, I have found it necessary to make a study of this material. I am indebted to Dr. Copeland for arranging to have the type specimens loaned to me for this purpose.